USING HIDDEN MESSAGE WORD SEARCHES METHOD IN TEACHING ENGLISH VOCABULARY - Melisa Novianty (Language and Education Journal, 2020)
The purpose of the study was to know whether using Hidden Message Word Searches could show better achievement in vocabulary or not. In this study, there were two groups in this study, such as: experimental and control groups. In other word, the samples were two classes (VIII.2 and VIII.3) in academic year 2011/ 2012. The writer chose them based on their report book and the same teacher of English. The techniques for collecting the data used test and questionnaire. The writer used the quasi-experimental design. As the results, this strategy showed that there was a significant difference between the students who were taught by using hidden message word searches than those who were not. Finally, the results of questionnaire indicated that this strategy was very beneficial as teaching media in vocabulary